Understanding the Factors Driving Farmers to Adopt Peer-to-Peer Lending Sharing Economy - Septiani, Hera Laxmi Devi; Sumarwan, Ujang; Yuliati, Lilik Noor; Kirbrandoko, Kirbrandoko (International Review of Management and Marketing, 2020)
Peer-to-peer (P2P) lending is one of the forms of sharing economy offered by Fintech as an alternative solution to address the limited access of smallholder farmers to financing sources but its adoption is relatively low despite its numerous benefits. It is, however, important to understand the factors driving farmers to adopt this system. Therefore, this study was conducted to investigate the factors influencing the behavioral intention of farmers to adopt farming financing P2P lending using UTAUT2 and Theoretical Model of Participation variables as well as other variables in the form of values in the Sharing Economy. Data was collected from 371 farmers in West Java, Indonesia that has not adopted farming financing P2P lending and analyzed using Structural Equation Modelling. The results showed eight variables have significant correlation and they include effort expectancy, social influence, hedonic motivation, price value, habit, perceived risk, values, and trust through the application of perceived risk as an intervening variable. This means it is important for the P2P lending provider to educate the farmers on the easiness of using the platform, provide evidence for its legitimacy, and show that its security is guaranteed. It is also important to share the success story of the adopter farmers to encourage the non-adopters to embrace P2P lending. Keywords: Consumer Behavior, Peer-to-peer Lending, Sharing Economy, Technology Adoption, UTAUT2 JEL Classification: M31 DOI: https://doi.org/10.32479/irmm.10564